Atom Probe Tomography investigations of microstructural evolution in an aged nickel superalloy for exhaust applications - Gardner, H; Pedrazzini, S; Douglas, J; De Lille, D; Moody, M; Bagot, P (Springer Nature, 2019)
The formation and evolution of nanoscale γ″ (Ni 3 (Nb, Ti, Al)) precipitates formed during thermal aging in the nickel superalloy Inconel 625 has been characterized using Atom Probe Tomography. The onset of γ″ precipitation has been found to occur after only one hour, markedly shorter than the aging time reported in the current literature. Evolution of precipitate composition and morphology during aging has been analyzed, and the potential onset of the γ″ → δ (Ni 3 (Nb, Mo, Cr, Fe, Ti)) transformation after long aging times is discussed.